Decarbonizing Automotive Supply Chains: Willingness to Pay for Green Steel (H2-DRI-EAF) - An Analysis of Green Premiums in the North American Automotive Industry - Björsne,Vilma; Cederlund,Elsa (2025)
As decarbonization pressures increase for energy-intensive processing industries, understanding demand side readiness is essential in order to scale up breakthrough technologies. This thesis investigates the willingness to pay (WTP) for green steel in the North American automotive industry, with a focus on steel produced by the H2-DRI-EAF route, where hydrogen is produced from renewable electricity. The study employs a triangulated qualitative research design integrating: (1) B2B insights from 25 semi-structured interviews with automotive OEMs and industry experts; (2) B2C insights derived from survey data on end- consumer WTP and (3) market insights from supply–demand dynamics and existing green premium patterns in North America and abroad. This multi-perspective approach thoroughly assesses OEMs’ WTP for green steel, while revealing the main systemic factors of a nascent green steel market in North America – where European premium structures prove not to be directly transferable. Results reveal that North American WTP for green steel exists but is highly conditional. While the automotive sector is structurally positioned to lead green steel adoption, as it currently relies on high-quality primary emission-heavy steel and face growing climate commitments, it remains in a state of strategic hesitation with no first-mover responsibility. However, a niche demand is building and from a market dynamics perspective, a green premium appears structurally justified as H2-DRI-EAF steel, critical for high- quality components, will most likely be in limited supply by 2030. However, this supply gap is potentially mitigated with “hydrogen-ready” NG-DRI capacity ready to shift into hydrogen when prices drop below those for natural gas. The research finds that WTP estimates accumulate at levels around ~20% above conventional steel prices, for steel with CO2 reduction levels at 90%. However, significant untapped potential is identified in the end consumer value pool, with an estimated 51% premium mismatch between what OEMs and end consumers are willing to pay for green steel vehicles. In fact, a green steel premium potential up to 71% is identified when transforming end consumer WTP into theoretical B2B WTP figures, especially among high-income EV buyers. Lower or no WTP is identified for steel with ~50% emissions reductions, which reflects the carbon intensity of widely available scrap-based EAF steel, a process already perceived as “green” among most OEMs and sold at no premium in North America. However, the empirical findings suggest that WTP is conditional and shaped by concerns over premium duration, risk exposure, scalability, and the lack of cost pass-through mechanisms or policy incentives. Still, WTP remains present where green steel contributes to value-driving needs, such as high-strength structural components, sustainable branding, and climate target alignment. In short, this paper contributes to the knowledge base on green steel adoption by investigating the demand side readiness for such a first-of-a-kind product as H2-DRI-EAF, which is an essential technology to decarbonize hard-to-abate sectors such as primary steelmaking. Patterns linked to the found WTP create a clear picture: In the green steel market in North America clear definitions, value chain transparency, and targeted a legislative landscape will play a critical role in turning a latent willingness to buy- and pay into a catalyst for systemic change.
Keywords: Green steel; Willingness to Pay; Green premium; H2-DRI-EAF; Automotive industry; Steel decarbonization; Hard-to-abate; North America